Analisa Respon Mekanis Bahan Dashboard Mobil dengan Metode Pengujian Tarik (Tensile Test) - Doli Tryono Siregar; Ade Irwan; Din Aswan Amran Ritonga (JITEKH, 2023)
Dashboard is a panel on the front of the car interior, here usually there are several facilities, such as instrumentation panels, drawers, radio / tape, and air conditioning. The dashboard also has many functions as a place for instrument panels and warning signal gauges and also has an audio system, ventilation air-conditioning head and many others. And here the researcher wants to know the strength on the car dashboard by using the tensile test method. Tensile testing is one such test. The method used in this research is a tensile test method using a UTM machine. Material testing machine with a length of 100 mm using ASTM E8. The results of the study have 5 specimens for the first specimen on the car dashboard having a tensile stress with a value of 33,95 Mpa strain with a value of 0,02 And the modulus of elasticity with a value of 1.697,5 Mpa the second specimen on the car dashboard has a tensile stress with a value of 35,98 Mpa strain with a value of 0,03 And the modulus of elasticity with a value of 1.199,33 Mpa The third specimen on the dashboard of the car has a tensile stress with a value of 43,55 Mpa strain with a value of 0,01 And the modulus of elasticity with a value of 4.345 Mpa the fourth specimen on the car dashboard has a tensile stress with a value of 33,95 Mpa strain with a value of 0,01 And the modulus of elasticity with a value of 3.395 Mpa the fifth specimen on the car dashboard has a tensile stress with a value of 42,77 Mpa strain with a value of 0,02 and modulus of elasticity with a value of 2.138,5 Mpa